SUSTAINABLE GROWTH AND LIQUIDITY ON PROFITABILITY: A STUDY ON MINING SECTOR COMPANIES LISTED AT INDONESIA STOCK EXCHANGE IN 2018 - Manullang, Shekinah Vitareyn; Hutabarat, Francis (Jurnal AKSI (Akuntansi dan Sistem Informasi), 2020)
This study aims to determine the effect of sustainable growth and liquidity on profitability, sustainable growth on profitability, and liquidity on profitability. The data used are quantitative in the form of financial statements on the Indonesia Stock Exchange in 2018. The population conducted in this study are companies listed on the Indonesia Stock Exchange. And the sample of this research is mining sector companies listed on the Indonesia Stock Exchange in 2018 and the population used is 40 companies. The variables used in this study are sustainable growth and liquidity as independent variables. Profitability as the dependent variable. The research analysis uses statistical data that is descriptive statistics, correlation matrix, significant tests, regression analysis for research data in the mining sector. Test results show that there is a significant effect between sustainable growth rate and liquidity on profitability. And there is no significant effect between Liquidity on Profitability. Simultaneously states there is a significant influence between sustainable growth rate and Liquidity on the profitability of mining companies in the Indonesia stock exchange in 2018.